The identification of source regions of black carbon at a receptor site off the eastern coast of China - Guo, Q. F.; Min* Hu; Guo, S.; ZJ Wu; Hu, W. W.; Peng, J. F.; Hu, W.; Y.S. Wu; Yuan, B.; Q. Zhang; Y. Song (Atmospheric Environment, 2015)
The black carbon (BC) mass concentration and the particle chemical compositions were continually measured at Changdao Island, which is a regional receptor site off the eastern coast of China. This island is in the transport passage of the continental outflow to the Pacific Ocean when the East Asia monsoon prevails in the winter and spring. The campaign period was for March and April 2011, which corresponded to heating and non-heating periods in northern China. The effect of BC emission source regions on BC measured at Changdao Island between the heating and non-heating periods was determined by integrating the total potential source contribution function (TPSCF) model with the new monthly emission inventory in 2010 and the fire counts retrieved from MODIS during the campaign. BC concentrations were determined to be highest for similar times of day for both the heating and non-heating periods: 4.27 mu g m(-3) at 8:00 AM and 3.06 mu g m(-3) at 9:00 AM, respectively. The probable source regions for BC were primarily located in Shandong and Jiangsu provinces (and in other neighboring provinces) for both periods. However, the source regions for the non-heating period extended more to the north and southwest than those of the heating period. TPSCF values were correlated with the emission rates from residential, industry, transportation, and power plants sources in the anthropogenic emission inventory. This correlation provides an indirect and qualitative process to verify the emission inventory. In the heating period, the predominant source was the residential source in the emission inventory, and this source had a significant effect on the BC concentration. The differing peak concentrations between the two periods may be observed because of the increased residential heating during the heating period, which suggested that the measures employed by the government and environmental managers to reduce the emissions of pollutants should be stricter in the identified source regions during the heating period. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: atmospheric aerosol; black carbon; changdao island; combustion; dispersion; emissions; intex-b; mercury; pm2.5; polycyclic aromatic-hydrocarbons; residential source; source regions; sulfur; tpscf; Transport